Assessment of Healthcare Waste Management Practices at Seti Provincial Hospital, Nepal - Joshi, Bidya; Sharma, Jiban; Joshi, Bimala; Thapa, Luna; Awasthi, Mahesh Prasad; Joshi, Tark Raj; Joshi, Keshab Raj; Pant, Ramesh Raj (Nepalese Journal of Development and Rural Studies, 2024)
Globally, healthcare waste (HCW) is recognized as the second most hazardous type of waste after radioactive materials. Improper management of HCW poses significant risks to healthcare workers, patients, surrounding communities, and the environment. This study aims to assess the current status of HCW generation and management at Seti Provincial Hospital in Nepal. Conducted over a 15-day period, the study evaluated the quantity and handling practices of HCW within the hospital. The waste collected was categorized into hazardous and non-hazardous types. The average HCW generation rate was found to be 0.55 kg per patient per day, with 65.98% classified as non-hazardous and 34.02% as hazardous. Findings indicate that the hospital’s HCW management practices require significant improvement. To ensure sustainable and safe waste handling, the adoption of scientifically sound and environmentally responsible methods for segregation, collection, transportation, storage, and disposal is strongly recommended.